Experimental and Analytical Modeling for Depth and Width of Cut Based on Regression Analysis using CO2 Laser Process Parameters - Aakif Anjum, A. A. Shaikh (International Journal of Advanced Science and Technology, 2020)
Laser beam machining is an advanced manufacturing technique used for machining the parts which are difficult to machine using conventional manufacturing process. In this paper CO2 laser is used to cut the acrylic by varying input parameters like power, speed and number of passes. The effect of input parameters on depth and width of cut is studied. Single pass of laser is not sufficient to get the desired depth and width of cut. Hence numbers of passes are varied from 20 to 60 to study the variation on depth and width of cut. An analytical model is developed and compared with experimental depth and width of cut. Analytical model shows close agreement with experimental depth and width of acrylic. It is concluded that maximum depth and width of cut can be obtained for high power and low-speed combination.